2020
DOI: 10.3892/ol.2020.12115
|View full text |Cite
|
Sign up to set email alerts
|

Two common polymorphic variants of OATP4A1 as potential risk factors for colorectal cancer

Abstract: Genetic variations in the organic-anion-transporting polypeptide (OATP)-encoding solute carrier of organic anions (SLCO) genes can promote cancer development and progression. The overexpression of solute carrier organic anion transporter family member 4A1 (OATP4A1), a transporter for steroid hormones, prostaglandins, and bile acids, has been previously associated with tumor recurrence and progression in colorectal cancer (CRC). Therefore, the present study aimed to investigate the association between 2 frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Falkowski et al have shown that the A388G variant genotypes of SLCO1B1 were not associated with colorectal cancer (CRC); similar results were obtained by Özhan et al in colorectal cancer [21,42]. In another study on two common polymorphisms of OATP4A1, no association between CRC predisposition and tumor recurrence was found [38]. Noci et al showed that A388G is associated with overall survival for patients with metastatic CRC treated with irinotecan.…”
Section: Discussionmentioning
confidence: 70%
“…Falkowski et al have shown that the A388G variant genotypes of SLCO1B1 were not associated with colorectal cancer (CRC); similar results were obtained by Özhan et al in colorectal cancer [21,42]. In another study on two common polymorphisms of OATP4A1, no association between CRC predisposition and tumor recurrence was found [38]. Noci et al showed that A388G is associated with overall survival for patients with metastatic CRC treated with irinotecan.…”
Section: Discussionmentioning
confidence: 70%
“…Falkowski et al have shown that the A388G variant genotypes of SLCO1B1 were not associated with colorectal cancer (CRC); similar results were obtained by Özhan et al in colorectal cancer 24,42 . In another study on two common polymorphisms of OATP4A1, no association with CRC predisposition and tumor recurrence was found 41 .…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, expression levels of these in ux transporters may play a crucial role in chemoresistance mechanisms 26 . Patients with OATP polymorphisms have been found to have altered pharmacokinetics due to their impact on absorption, distribution, and excretion of anticancer drugs, thus cancer outcomes 15,23,24,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Sanger sequencing revealed that the heterozygous mutation g.323G>A (p.Val78Ile), previously described in colon cancer and healthy control patients, was present in 2 out of 7 investigated cell lines. This SNP, which is located in the first intracellular loop of the protein distant to the binding site of drugs, was previously shown to have no effect either on the expression levels nor on the uptake of the OATP surrogate substrate sodium-fluorescein ( Buxhofer-Ausch et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%